2023
DOI: 10.3390/nanomanufacturing3040026
|View full text |Cite
|
Sign up to set email alerts
|

Nanoimprinted Hierarchical Micro-/Nanostructured Substrates for the Growth of Cardiomyocyte Fibers

Michael M. Mühlberger,
Sonja Kopp,
Alison A. Deyett
et al.

Abstract: Investigating the behavior of cardiomyocytes is an important part of drug development. We present a structure and a related nanoimprint-based fabrication method, where the cardiomyocytes form isolated fibers, which is beneficial for drug testing, more closely representing the structure of the cardiomyocytes in vivo. We found that channel structures with walls with a rough top surface stimulate cardiomyocytes to form such fibers, as desired. Nanoimprint lithography is used as a fast and cost-efficient method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…In addition, two different microgrooved structures with a groove width of = 6 µm and a ridge width of = 4.5 µm (NIL-3) as well as = 3 µm and = 2.5 µm (NIL-4) with a height of 10 µm ( Figure 5 b), were replicated. This type of structure, where the groove width is commonly larger or equal to the size of a single cell, can allow cell attachment and migration, as well as cell alignment following the geometrical guidance [ 56 ]. Several studies demonstrated that cells subjected to microgroove substrates were significantly more elongated and significantly more aligned on microgroove substrates surfaces with topographical cues as compared to those on smooth surfaces [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, two different microgrooved structures with a groove width of = 6 µm and a ridge width of = 4.5 µm (NIL-3) as well as = 3 µm and = 2.5 µm (NIL-4) with a height of 10 µm ( Figure 5 b), were replicated. This type of structure, where the groove width is commonly larger or equal to the size of a single cell, can allow cell attachment and migration, as well as cell alignment following the geometrical guidance [ 56 ]. Several studies demonstrated that cells subjected to microgroove substrates were significantly more elongated and significantly more aligned on microgroove substrates surfaces with topographical cues as compared to those on smooth surfaces [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%